(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the use of representatives of the mavrak group in medicine and their importance in human life. Marmarakis a genus of perennial plants or semi-shrubs. The homeland of representatives of the Marmarak genus is considered to be the shores of the Mediterranean Sea. Marmarakplant belongs to the Lamiaceae L - family of sedges, Salvia L. - sage, marmarak, flax family. In Latin "salvara" means to heal. Most species of the category are used for therapeutic purposes. Representatives of this category are annual and perennial grasses, shrubs, and in tropical countries, shrubs and trees. Lamiaceae (L.)is a large family consisting of 170 genera and 3400 species, distributed mainly in warm and temperate regions.